Philippines-Japan Free Trade Agreement: Analyzing Its Potential Impact Using a Computable General Equilibrium Model - Taeko Yasutake (Philippine Institute for Development Studies (PIDS), 2004)
This study analyzes the potential impact of the Philippines-Japan Free Trade Agreement (FTA) on the Philippine economy in case of the Philippines' discriminately unilateral tariff reduction on import from Japan using a computable general equilibrium model for the Philippine economy. The result of the assessment of this study indicates that even only a reduction of tariff rates on imports from Japan would expand the Philippines' import from Japan and in total by 2.36-8.58 and 0.35-0.61 percent, respectively. Consumer welfare measured in Compensated and Equivalent Variation increase in all of 5 households classified by income level, not in a proportional way for each household however. More favorable impact on all households would be expected if not only a tariff reduction but also other factors such as liberalization of foreign investment are included in the agreement.
Keywords: 330; computable general equilibrium (CGE); foreign investment; Philippines-Japan free trade agreement; unilateral tariff reduction; consumer welfare; Freihandelszone; Importnachfrage; Auslandsinvestition; Wohlfahrtsanalyse; Philippinen; Japan; CGE-Modell; Wirkungsanalyse